Culture-Based Short Story Learning for Strengthening Students’ Patriotic Character - Muhammad Eza Maulana; Muhammad Ainun Najib; Latif Syaipudin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Literature-based character education is essential for strengthening students’ cultural awareness and national identity. Specific Background: Despite its potential, the use of culture-based short stories in Indonesian language learning is often not optimally aligned with students’ sociocultural contexts. Knowledge Gap: Few studies have examined how locally rooted short stories function as contextual tools for cultivating patriotism within madrasah-level education. Aims: This study analyzes the use of two cultural short stories—“Yogyakarta” and “Mencintai Budaya Sendiri”—to reinforce patriotic character values among students at MTs Darul Falah Sumbergempol. Results: The findings show that “Yogyakarta” fosters religiosity, curiosity, perseverance, and appreciation for national heritage, while “Mencintai Budaya Sendiri” strengthens cultural pride, tolerance, responsibility, and identity preservation. Integrating both texts increased students’ reading interest, cultural awareness, and patriotic attitudes. Novelty: This research demonstrates that local literary works serve not only as aesthetic reading materials but also as effective instruments of cultural resistance amid globalization by embedding contextual, relatable values. Implications: Schools are encouraged to adopt local culture–based literature to enhance character education, support literacy improvement, and reinforce national identity among the younger generation. Highlights: Use of local culture–based short stories to strengthen students’ patriotic character Integration of “Yogyakarta” and “Mencintai Budaya Sendiri” increases reading interest and cultural awareness. Shows that local literature can act as an effective, contextual medium for character education in the digital/global era. Keywords: Short Stories, Character Education, Patriotism, Indonesian Language Learning, Local Culture